A Protocol for the Non-invasive Method of Ultrasound Separation During the Sociosexual Vocal-Non-contact Model in Rats - Bogacki-Rychlik, Wiktor; Wrona, Anna; Bialy, Michal (Frontiers in Behavioral Neuroscience, 2022)
Ultrasonic vocalization (USV) is one of the measurable behavioral parameters of socio-sexual interactions in rats. To precisely and accurately describe the neurobehavioral properties of USV and the potentially related specific emotional responsiveness of animals, we need to know which animals vocalize and what is their exact behavioral and physiological response. To this end, we modified the noncontact cage (noncontact erection model, NCE) by adding a modification (vocalization-noncontact erection, VOC-NCE) that makes it possible to assign emitted ultrasonic signals to a particular animal. Typically, the NCE cage consists of two compartments separated by perforated baffles. A male is placed in one section and a receptive female is placed in the other section. This makes possible the accurate description of sexual parameters related to the cues controlled by the experimenter. In VOC-NCE, we completely separated the male USV from the female USV by three appropriately perforated baffles and located microphones combined with ultrasonic screening. We recorded emission in both typical bands, the so-called 22-kHz and 50-kHz bands, with various subtypes, thus highlighting the utility of our protocol to investigate the sexual dimorphism of vocalization. Similar to the anticipatory model, we showed that emission can occur without acoustic feedback from concomitants during the VOC-NCE test. Therefore, we propose a relatively simple method for assigning individual vocalization. We discuss its usefulness and its limitations in assessing vocal differentiation related to sexual parameters, adaptive changes during conditioning procedures, and further applications.